An investigation on How Community Pharmacies and Herbalist's Shops manage patients with probable Oral Cancer - M Rabiei; F Yousefbeyk; S Ghasemi; S Pirzamanbin (Islamic Azad University, 2016)
Background and aim: Oral cancer is a serious health problem, mainly in cases with late diagnosis. The objective of this study was to investigate the role of community pharmacists, community pharmacy assistants and herbalists in late stage diagnosis of oral cancer. Materials and Methods: A cross-sectional study by the standardized simulated patient approach was undertaken to investigate the recommendation given to a potential cancer patient at pharmacies and herbalists' shops in Rasht, Iran. The introductory statement was "My father is 63 years old and he is a smoker who has a painful ulceration on his tongue for about 6 months which wasn't painful at first but is painful now. What would be your recommendation? "All the responses were noted and transferred to data sheets. The recommendations were analyzed separately and then grouped. Recommended therapies and their administrations were also recorded. Results: The results showed that 73% of community pharmacies referred patients to primary medical care systems. Community pharmacists and community pharmacy assistants had closely equal roles (74.3% and 72.5%, respectively). Contrariwise, only 7.1% of herbalists referred patients with oral ulcers to a physician or a dentist. Almost 10% of the pharmacies recommended OTC drugs only and 11% prescribed medications combined with referral to a medical or dental practitioner for consultation. In reverse, 78.6% of herbalists recommended an OTC remedy and none of them advised patients to visit a GP or dentist accompanied by prescribing an herbal remedy. Conclusions: Herbalists have a potential role in diagnostic delay in patients with oral cancer.